The Effects of Geopolitical Risks on Firm Investments: An Empirical Study on the Istanbul Stock Exchange - Selim Süleyman; Yeşim Şendur; Yaşar Tınar (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)

(untitled)
Extensive research has been conducted on the factors that influence a company's investment decisions. Both country-specific and firm-specific factors, impacting firms' investment choices, have been identified by researchers. Firm-specific factors encompass profitability, size, operating risk, liquidity, and growth potential. On the other hand, country-specific factors are delineated as economic growth, inflation, political and economic uncertainty, taxation, and legal regulations within the country. Literature studies suggest that, in addition to political and economic uncertainties, geopolitical risks also exert a significant influence on firms' investment decisions. The research below focuses on how geopolitical risks (GPR) affect the investing choices of 309 non-financial businesses included in the Istanbul Stock Exchange of Turkey. Data spanning ten years, from 2010 to 2019, was collected, and the unbalanced panel data method was employed for analysis. In light of the study's conclusions, an increase in Turkey's GPR Index corresponded to a decline in firm investments, aligning with expectations.